Meningkatkan Daya Kreativitas Siswa Melalui Model Pembelajaran Kooperatif Type Stad - Lailatuz Zahro; Musdalifah Rojabiyah; Arinda Usmania (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2023)
The aims of this research are 1) to describe the implementation of the STAD type cooperative learning model 2) to describe the supporting and inhibiting factors for teachers in implementing the STAD type cooperative learning model. in PAI learning at SMAN 1 Kejayan. The research method uses a descriptive qualitative type using observation, interview and documentation data collection techniques. The results of the research are that the PAI learning process at SMAN 1 KEJAYAN uses the STAD cooperative method, the teacher first delivers the material, then students are formed into several groups and each group gets questions that must be discussed. Meanwhile, supporting factors in implementing the STAD learning model are 1) conducive conditions and situations for students, 2) students are more enthusiastic in participating in learning, 3) students are more active. Meanwhile, factors that hinder learning are 1) there are students who pay more attention to their cell phones than their teachers, 2) lack of teacher creativity in providing PAI material.